A Functional Model for the Development of Intercultural Communication Competence for a Future Russian Language Teacher - Yusupova F.M. (Euro Asian Journal Publishing, 2024)
This article describes the problem of the relevance of intercultural competence of a teacher in a multinational state
Keywords: Pedagogical models; competence; educational-cognitive; reproductive-problematic